The Moderating Role of Debt To Asset Ratio, Asset Turnover, and Company Size on the Influence of Islamic Social Reporting (ISR) Towards Financial Performance - Khusna, Atiatul; Imanda Firmantyas Putri Pertiwi (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to examine the influence of Islamic social reporting (ISR) on financial performance (FP), with debt-to-asset ratio (DAR), asset turnover (AT), and company size (CS) as moderating variables. Design/methodology/approach: This research adopts a quantitative approach by conducting data analysis from the annual reports of manufacturing companies indexed in ISSI for the years 2020-2022, totaling 80 companies. The sampling technique employed is purposive sampling. Data analysis is conducted using Eviews software. Research Findings: The research findings indicate that asset turnover and company size have a significant positive effect on financial performance, while Islamic social reporting and debt to asset ratio do not have a significant effect on financial performance. Furthermore, the results suggest that asset turnover moderates the relationship between Islamic social reporting and financial performance, whereas debt to asset ratio and company size do not moderate the relationship between Islamic social reporting and financial performance. Theoretical Contribution/Originality: This research provides information and insights to investors and companies regarding the factors influencing the financial performance of a company, thus serving as a basis for investment decision-making.